Caffeine and Chlorogenic Acid Combination Attenuate Early-Stage Chemically Induced Colon Carcinogenesis in Mice: Involvement of oncomiR miR-21a-5p - Bartolomeu, Ariane Rocha [UNESP]; Romualdo, Guilherme Ribeiro [UNESP]; Lisón, Carmen Griñán; Besharat, Zein Mersini; Corrales, Juan Antonio Marchal; Chaves, Maria Ángel García; Barbisan, Luís Fernando [UNESP] (MDPI, 2022)
Colorectal cancer (CRC) is one of most common cancers worldwide, with high rates of mortality. Epidemiological findings demonstrate that coffee consumption reduces the risk of developing CRC by ~13%. In general, in vivo and in vitro findings demonstrate the antiproliferative, antioxidant and proapoptotic effects of brewed coffee or major bioavailable coffee compounds. Thus, it was assessed whether caffeine (CAF) and/or chlorogenic acid (CGA) attenuates the early-stage of chemically induced mouse colon carcinogenesis. Male Swiss mice were submitted to a 1,2-dimethylhydrazine/deoxycholic acid (DMH/DCA)-induced colon carcinogenesis model. These animals received CAF (50 mg/kg), CGA (25 mg/kg) or CAF+CGA (50 + 25 mg/kg) intragastrically for five times/week for ten weeks. CAF+CGA had the most pronounced effects on decreasing epithelial cell proliferation (Ki-67) and increasing apoptosis (cleaved caspase-3) in colonic crypts. This treatment also decreased the levels of proinflammatory cytokines IL-6, IL-17 and TNF-α, and downregulated the oncomiR miR-21a-5p in the colon. Accordingly, the analysis of miR-21a-5p targets demonstrated the genes involved in the negative regulation of proliferation and inflammation, and the positive regulation of apoptosis. Ultimately, CAF+CGA attenuated preneoplastic aberrant crypt foci (ACF) development. Our findings suggest that a combination of coffee compounds reduces early-stage colon carcinogenesis by the modulation of miR-21a-5p expression, highlighting the importance of coffee intake to prevent CRC.
Keywords: caffeine; chemically induced colon carcinogenesis; chlorogenic acid; mice; miRNA expression